2001
DOI: 10.1021/om010566b
|View full text |Cite
|
Sign up to set email alerts
|

Ti(NMe2)4 as a Precatalyst for Hydroamination of Alkynes with Primary Amines

Abstract: Hydroaminations of carbon-carbon triple bonds with primary amines are catalyzed with commercially available Ti(NMe 2 ) 4 . The reaction is surprisingly fast with many substrates and often selective for the Markovnikov product with terminal alkynes. The scope of the catalysis was investigated with a variety of amines and alkynes; arylamines and 1-hexyne were found to be especially good substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
71
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 16 publications
1
71
2
Order By: Relevance
“…[9] The solidstate structure surprisingly reveals a highly unsymmetrical and strongly distorted octahedral geometry around the titanium centre. This finding is in sharp contrast to a comparable control experiment performed with [Ti(NMe 2 ) 4 ] as the hydroamination catalyst, [10] which resulted in the formation of a 93:7 mixture of regioisomers 5a and 5b (91 % yield). In the presence of 5 mol-% 2, the reaction goes to completion within 24 h at 80°C and, after subsequent reduction (NaBH 3 CN/ZnCl 2 ), the product 5a could be isolated in 97 % yield (Table 1, entry 3).…”
Section: Resultscontrasting
confidence: 92%
“…[9] The solidstate structure surprisingly reveals a highly unsymmetrical and strongly distorted octahedral geometry around the titanium centre. This finding is in sharp contrast to a comparable control experiment performed with [Ti(NMe 2 ) 4 ] as the hydroamination catalyst, [10] which resulted in the formation of a 93:7 mixture of regioisomers 5a and 5b (91 % yield). In the presence of 5 mol-% 2, the reaction goes to completion within 24 h at 80°C and, after subsequent reduction (NaBH 3 CN/ZnCl 2 ), the product 5a could be isolated in 97 % yield (Table 1, entry 3).…”
Section: Resultscontrasting
confidence: 92%
“…Note that the intermolecular hydroamination of alkynes using 2 yields preferentially the Markovnikov product. 8 As the sterogenic centers of the imine products are not generated during the catalytic hydroamination reaction, a potential kinetic resolution has yet not been intensively investigated. Instead, the conversion of 1,3-disubstituted aminoallenes 11 should constitute an appropriate tool to explore asymmetric catalysis.…”
mentioning
confidence: 99%
“…

Studies of preparation and characterisation of titanium amidoand imido-complexes have largely been driven by investigation of hydroamination reaction, in which an amine is added across an unsaturated C-C bond to form imines, enamines and N-containing heterocycles. [19][20][21][22][23][24] As a continuation of our efforts on studying the hydroamination of alkynes catalysed by pyrrolyl ligand-chelated titanium compounds, 25-27 we are exploring the syntheses and catalytic activities of titanium amido-or imido-complexes chelated by H 2 pmpmi [H 2 pmpmi = (2-pyrrolylmethene)-(2pyrrolylmethyl)imine]. 1-7 A variety of complexes are known to effect such transformations.

…”
mentioning
confidence: 99%
“…2 Amongst these, titanium complexes have been proved to be some of the most useful catalysts for the hydroamination of alkynes due to their enhanced stability and improved functional group tolerance. [19][20][21][22][23][24] As a continuation of our efforts on studying the hydroamination of alkynes catalysed by pyrrolyl ligand-chelated titanium compounds, [25][26][27] we are exploring the syntheses and catalytic activities of titanium amido-or imido-complexes chelated by H 2 pmpmi [H 2 pmpmi = (2-pyrrolylmethene)-(2pyrrolylmethyl)imine]. [8][9][10][11][12][13][14] This research has indicated that the ligand chelating to the metal centre plays a key role in controlling the regioselectivity of the hydroamination products.…”
mentioning
confidence: 99%